Different modulation of TRAIL-induced apoptosis by inhibition of pro-survival pathways in TRAIL-sensitive and TRAIL-resistant colon cancer cells - Vaculová, Alena; Hofmanová, Jirina; Soucek, Karel; Kozubík, Alois (FEBS letters, 2006)
Epithelial cells can be manipulated to undergo apoptosis depending on the balance between pro-survival and apoptotic signals. We showed that TRAIL-induced apoptosis may be differentially regulated by inhibitors of MEK ERK (U0126) or PI3K/Akt (LY294002) pathway in TRAIL-sensitive (HT-29) and TRAIL-resistant (SW620) human epithelial colon cancer cells. U0126 or LY294002 significantly enhanced TRAIL-induced apoptosis in HT-29 cells, but not in SW620 cells. We report a different regulation of the level of an anti-apoptotic Mcl-1 protein under MEK/ERK or PI3K/Akt pathway inhibition and suggest the mechanisms involved. A special attention was paid to the role of the ERK1/2, Akt, and glycogen synthase kinase 3beta.
Keywords: Cell Survival; Phosphorylation; Apoptosis; Extracellular Signal-Regulated MAP Kinases; nádorové proteiny; kinasa 3 glykogensynthasy; Humans; nádory tračníku; fosforylace; buňky HT-29; Phosphoinositide-3 Kinase Inhibitors; mitogenem aktivovaná proteinkinasa 1; Colonic Neoplasms; mitogenem aktivovaná proteinkinasa 3; mitogenem aktivované proteinkinasy kinas; HT29 Cells; inhibitory fosfoinositid-3-kinasy; lidé; protein MCL-1; Mitogen-Activated Protein Kinase 3; Enzyme Activation; Proto-Oncogene Proteins c-bcl-2; protein TRAIL; apoptóza; protoonkogenní proteiny c-akt; kinasa glykogensynthasy 3beta; Proto-Oncogene Proteins c-akt; Mitogen-Activated Protein Kinase Kinases; Glycogen Synthase Kinase 3 beta; TNF-Related Apoptosis-Inducing Ligand; Caspase 8; Poly(ADP-ribose) Polymerases; poly(ADP-ribosa)polymerasy; inhibitory enzymů; kaspasa 8; keratin-18; extracelulárním signálem regulované MAP kinasy; Myeloid Cell Leukemia Sequence 1 Protein; aktivace enzymů; Neoplasm Proteins; Mitogen-Activated Protein Kinase 1; protoonkogenní proteiny c-bcl-2; Enzyme Inhibitors; viabilita buněk; Keratin-18; Glycogen Synthase Kinase 3